2013
DOI: 10.1016/j.jcrimjus.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and environmental overlap between aggressive and non-aggressive antisocial behavior in children and adolescents using the self-report delinquency interview (SR-DI)

Abstract: Purpose This study investigated genetic and environmental commonalities and differences between aggressive and non-aggressive antisocial behavior (ASB) in male and female child and adolescent twins, based on a newly developed self-report questionnaire with good reliability and external validity – the Self-Report Delinquency Interview (SR-DI). Methods Subjects were 780 pairs of twins assessed through laboratory interviews at three time points in a longitudinal study, during which the twins were: (1) ages 9–10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…In addition, longitudinal genetic and environmental influences were studied. In these more recent studies, sex differences were observed when different self‐report measures were implemented, with boys showing considerably higher heritability estimates than girls, especially around and after adolescence [Baker et al, ; Wang et al, ]. Mother and teacher ratings did not result in sex differences of heritability measures.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, longitudinal genetic and environmental influences were studied. In these more recent studies, sex differences were observed when different self‐report measures were implemented, with boys showing considerably higher heritability estimates than girls, especially around and after adolescence [Baker et al, ; Wang et al, ]. Mother and teacher ratings did not result in sex differences of heritability measures.…”
Section: Methodsmentioning
confidence: 99%
“…This pattern of findings would suggest direct genetic effects on aggressive behavior, whereas the etiology of rule-breaking behavior is predicted more strongly by the interplay between genes and environment. Earlier evidence also suggests that the genetic overlap between the two subtypes of externalizing behavior is only moderate, which could indicate that different genes contribute to each subtype (Wang et al 2013). A molecular genetic study by Burt and Mikolajewski (2008) examined this hypothesis and found a direct effect of DAT1 specifically for rule-breaking behavior.…”
Section: Distinguishing Informants and Subtypes Of Externalizing Probmentioning
confidence: 99%
“…The illustration presented below uses a sum score of all available items because both versions of the CBCL subscale aim to measure the same underlying construct of physical aggression across all ages and because composite scores of slightly varying item sets are often used in practice (Forsman et al, 2010; Wang et al, 2013; van Beijsterveldt et al, 2003). To assess the consequences of this approach, the bias attributable to using a sum score of all available items is calculated for hypothetical growth parameters in an LGM.…”
Section: Empirical Illustrationmentioning
confidence: 99%
“…In longitudinal settings, however, the meaning of a measurement instrument may change over time, and different questions may be asked to address age-appropriate expressions of the same behavior (Achenbach & Rescorla, 2000, 2001; Edwards & Wirth, 2009; Hudziak et al, 2003; Rutter & Sroufe, 2000). When constructing a simple phenotype to analyze across multiple time points or ages, a common practice is to use a sum score or mean score that aggregates individual questionnaire items (e.g., Forsman et al, 2010; Hudziak et al, 2003; Wang et al, 2013; van Beijsterveldt et al, 2003). Although these scores are easy to compute and use, they are based on the assumption that all items are equally relevant indicators of the phenotype of interest, and they ignore the possibility that items can change in relevance over age.…”
mentioning
confidence: 99%